Squaramide—Naphthalimide Conjugates as “Turn-On” Fluorescent Sensors for Bromide Through an Aggregation-Disaggregation Approach - Kumawat, Lokesh K.; Abogunrin, Anthony A.; Kickham, Michelle; Pardeshi, Jyotsna; Fenelon, Orla; Schroeder, Martina; Elmes, Robert B. P. (Frontiers in Chemistry, 2019)
The syntheses of two new squaramide-naphthalimide conjugates (SQ1 and SQ2) are reported where both compounds have been shown to act as selective fluorescence ‘turn on’ probes for bromide in aqueous DMSO solution through a disaggregation induced response.